From Concept to Practice: The Reality of Religious Moderation in State Islamic Universities in Aceh - Razak, Abd; A. Rasyid, Saifuddin; Syah Putra, Rahmad; Khatami, M.; Muntazhar, Asyraf (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This study examines the implementation of Religious Moderation (Moderasi Beragama/MB) in State Islamic Higher Education Institutions (PTKIN) in Aceh, Indonesia, within the framework of national policy and local religious dynamics. Using empirical data and institutional analysis, the research identifies key structural and cultural factors affecting the success of this agenda. While the concept of moderation is compatible with Acehnese Islamic traditions, institutionalization remains limited due to its exclusion from strategic planning, inadequate funding, and varied reception among academic communities. UIN Ar-Raniry Banda Aceh stands out for its more structured and sustained approach, supported by strong leadership and resource commitment. In contrast, other PTKINs show fragmented, ad hoc efforts shaped by institutional and financial constraints. The study finds that localized strategies—rooted in contextual theology, cultural practices, and credible religious authority—are more effective in embedding moderation values within academic settings. These findings underscore that successful implementation of religious moderation in higher education depends on integrating policy with institutional will and cultural engagement, allowing national agendas to resonate meaningfully within diverse local contexts.